The Impact of Conceptual Change Texts on the Elimination of Misconceptions of Science Teacher Candidates about the Subject of Solutions - Deniz Altınışık; Gülşah Tanrıverdi; Murat Demirbaş; Yasemin Şahintürk (Sakarya University, 2013)
The aim of this study is to explore the impact of conceptual change texts on the elimination of science teacher candidates misconceptions about the subject of solutions. It is a semi-experimental study that is designed according to the pretest-posttest control group design. The data was collected using the Test for Detecting Misconceptions (TDM) prepared by the researchers, which consisted of 20 open-ended questions for which students were asked to reason their answers. A total of 45 third-grade students participated in the research, who study Science Teaching at Kırıkkale University and Ahi Evran University. Students' misconceptions about the subject of solutions were determined through TDM. The subject was lectured using conceptual change texts to experimental group students for three weeks, whereas it was taught to control group students using conventional teaching methods. TDM was administered again to experimental and control groups as posttest at the end of the study. The quantitative data of students' responses were analyzed using dependent and independent samples t-test in SPSS 15 software. Qualitative data, on the other hand, were analyzed separately by each researcher according to the categories they formulated using the content analysis method, and thus students' misconceptions were determined. It was determined that the use of conceptual change texts is significantly more effective than the use of the conventional teaching method in the elimination of students' misconceptions about the subject of solutions. Suggestions are presented in line with the findings obtained.